Comparison of Plastic Surgeon and Spine Surgeon Closure in Revision Short Segment Thoracolumbar Spinal Fusions. Issue 18 (15th September 2021) - Zhong, Jack; Balouch, Eaman; O'Malley, Nicholas; Maglaras, Constance; Stickley, Carolyn; Leon, Carlos; O'Connell, Brooke; Fischer, Charla R.; Protopsaltis, Themistocles; Buckland, Aaron J.
Abstract : Study Design: Retrospective cohort analysis. Objective: To compare outcomes of plastic versus spine surgeon wound closure in revision 1 to 4 level thoracolumbar fusions. Summary of Background Data: Plastic surgeons perform layered musculocutaneous flap closures in high-risk spine patients such as revision posterior spinal fusion and complex deformity correction surgeries. Few studies have assessed outcomes of revision fusion performed with plastic surgical closures, particularly in nondeformity thoracolumbar spinal surgery. Methods: A retrospective review of 1 to 4 level revision thoracolumbar fusion performed by Orthopedic or Neurosurgical spine surgeons. Patient charts were reviewed for demographics and perioperative outcomes. Patients were divided into two cohorts: wound closures performed by spine surgeons and those closed by plastic surgeons. Outcomes were analyzed before and after propensity score match for prior levels fused, iliac fixation, and levels fused at index surgery. Significance was set at P  < 0.05. Results: Three hundred fifty-seven (87.3%) spine surgeon (SS) and 52 (12.7%) plastic surgeon (PS) closures were identified. PS group had significantly higher number of levels fused at index (PS 2.7 ± 1.0 vs. SS 1.8 ± 0.9, P  < 0.001) and at prior surgeries (PS 1.8 ± 1.2 vs. SS 1.0 ± 0.9, P  < 0.001), and rate of iliac instrumentation (PS 17.3% vs. SS 2.8%, P  < 0.001). Plastics closure was an independent risk factor for length of stay  > 5 days (odds ratio 2.3) and postoperative seroma formation (odds ratio 7.8). After propensity score match, PS had higher rates of seromas (PS 36.5% vs. SS 3.8%, P  < 0.001). There were no differences between PS and SS groups in surgical outcomes, perioperative complication, surgical site infection, seroma requiring aspiration, or return to operating room at all time points until follow-up ( P  > 0.05 for all). Conclusion: Plastic spinal closure for 1 to 4 level revision posterior thoracolumbar fusions had no advantage in reducing wound complications over spine surgeon closure but increased postoperative seroma formation. Level of Evidence: 4 Abstract : Plastics surgeons are often called to close high-risk spine surgery patients include those undergoing revision spine surgery to reduce the risk of perioperative wound-related complications. This study compares surgical closures by spine surgeons versus plastic surgeons in revision 1 to 4 level thoracolumbar fusions.